From Picturebook to Multilingual Collage: Bringing Learners' First Language and Culture into the Pre-school Classroom - Emma McGilp (CLELEjournal, 2014)
This paper discusses a project with a small group of children learning English as an a language (EAL) at a pre-school in Scotland. The project however could be replicated across the globe, in any classroom with a diverse range of learners, with particular benefit to minority and newly arrived migrant children. At the project's core was the aim to bring the children's first language and culture into the classroom, drawing in particular on Cummin's (1984) Common Underlying Proficiency model, which asserts that knowledge of one language can assist learners in their acquisition of another. The project used multicultural picturebooks to validate the learner's experiences and culture, and then called on parents' funds of knowledge to make the children's first language visible in the classroom. This joint working between the children, parents and the pre-school culminated in the production of a multilingual collage - a prominent display that recognises the value of the children's first language in the classroom, builds bridges between home and school and is reflective, and proud, of an increasingly multilingual Scotland.